Pengembangan Pendidikan Kewirausahaan di Universitas Muhammadiyah Sidenreng-Rappang: Pendekatan Teori Efektuasi dan Business Model Canvas - Maichal Maichal; Erwin; Cindy Yoel Tanesia; Natali Ika Widjaya; Yuyun Karystin Meilisa Suade; Tony Antonio; Elia Ardyan (AMMA : Jurnal Pengabdian Masyarakat, 2023)
The purpose of this community service is to teach basic planning in entrepreneurship education through effectuation theory and the business model canvas (BMC). The dedication partner is Muhammadiyah Sidenreng-Rappang University. The participants were 18 lecturers and 32 students from Muhammadiyah Sidenreng-Rappang University. The theme of developing entrepreneurship education is where the focus of discussion is effectuation theory and the business model canvas. The result of this dedication is that students are able to apply effectuation theory and the business model canvas as part of their business planning. There are 8 groups that have a business model canvas planning. Activities are carried out by means of material presentation, discussion, mentoring, and competition. The results of this dedication significantly impacted the participants, who were enthusiastic about participating in the 3-day training. Participants also have unique ideas that can be implemented